Comparative Analysis of the Therapeutic Potential of Probiotics in Treating Psoriasis, Acne, and Atopic Dermatitis: A Systematic Review and Meta-Analysis - Fakhira Ahsan; Kashaf Ansari; Tanzeel Shafique Ul Rehman (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Probiotics have recently garnered attention for their ability to manage skin conditions, as they support the immune system, the gut-skin connection, and lower inflammation. This systematic review and meta-analysis sought to determine the effectiveness of oral probiotic supplementation to improve clinical outcomes in dermatological disorders such as psoriasis, acne, and atopic dermatitis.